The contested concept of growth imperatives: Technology and the fear of stagnation - Oliver Richters; Andreas Siemoneit (University of Oldenburg, Department of Economics, 2018)
Economic growth has become a prominent political goal worldwide, despite its severe conflicts with ecological sustainability. Are "growth policies" only a question of political or individual will, or do "growth imperatives" exist that make them "inescapable"? We structure the debate along two dimensions: (a) degree of coerciveness between free will and coercion, and (b) types of agents affected. Carefully derived micro level definitions of "social coercion" and "growth imperative" are used to discuss several mechanisms which are suspected to make economic growth necessary for firms, households, and nation states. We identify technological innovations as a systematic necessity to net invest, trapping firms and households in a positive feedback loop to increase efficiency. Due to its resource consumption, the competitive advantage of a novel technology is often based on a violation of the meritocratic principle. The resulting dilemma between "technological unemployment" and the social necessity of high employment can explain why states "must" foster economic growth. Politically, we suggest market compliant institutions to limit resource consumption and redistribute economic rents.
Keywords: D11; D13; E22; O44; P10; P12; P18; Q01; Z13; 330; economic growth; social coercion; growth imperative; technology; resource consumption; unemployment